IMPLEMENTING SEMANTIC IN IDENTIFYING TYPES OF TRANSLATION PROCEDURES FROM THE LIVE ACTION MOVIE "MULAN": IMPLEMENTASI SEMANTIC DALAM MENGIDENTIFIKASI JENIS PROSEDUR PENERJEMAHAN DARI FILM LIVE ACTION "MULAN" - Sihombing, Olvi Prihutami; Cici Theresia Malau; Grace Sella Veronika Hutagaol; Arina Madina Ibrahim (Jurnal Intelek Insan Cendikia, 2024)
In the framework of semantic analysis, this study attempts to determine the most common forms and methods of English to Indonesian translation texts in the motion picture "Mulan," with an emphasis on the meaning of translation ("meaning"). As a descriptive qualitative study, this research entails a thorough examination of the translation techniques used in the film. The information is made up of words, phrases, and other language components that may be found in the subtitles of the English and Indonesian versions of the movie. These details were carefully taken from the motion picture "Mulan." Document analysis is the method used in this study to collect data, which enables a detailed analysis of the text with subtitles. Using this approach, the research seeks to understand the ways in which meaning is expressed in different languages and which translation methods are most frequently employed. The study's conclusions show that it gets harder to convey the intended message successfully the larger the linguistic and cultural divide is between the source and target languages. The difficulties and nuances of translation work are brought to light in this study, especially when it comes to preserving the original text's semantic integrity while modifying it to meet the linguistic and cultural norms of the intended audience.